OR17. Clinical characteristics and risk factors of reduced ejection fraction in coronary artery disease patients undergoing percutaneous coronary intervention at sanglah hospital denpasar, bali, indonesia in 2021: a cross-sectional hospital-based study. (23rd November 2021) - Upadhana, P S; Jagannatha, G N P; Dewi, P I S L; Nolan, J; Pamungkas, K M N; Wijaya, A R; Wirawan, H
Abstract: Aims: This study was conducted to determine the clinical characteristics and risk factors of reduced ejection fraction (EF) in coronary artery disease (CAD) patients undergoing percutaneous coronary intervention (PCI). Methods and Results: Analytical observational study with a cross-sectional study design was conducted. All patients diagnosed with CAD and had a history of PCI at Sanglah Hospital from December 2020 – June 2021 were enrolled. Univariate analysis was performed to demonstrate the baseline characteristics of the patients. Chi-Square analysis was performed to determine the association between variables. Kruskal-Wallis analysis was performed to determine the differences in clinical characteristics between groups of patients based on the EF. There were 196 patients included in this study. Most of the patients were male (n = 135, 68.9%), with median age of 59 (22-81). The median of the EF was 59.2% (22-81). The most common comorbid found in the patients was hypertension (n = 108, 55.1%). Chi-Square analysis showed a significant association between hyperuricemia (p = 0.019; PR = 1.815; 95%CI= 1.163-2.831), arrhythmias (p = 0.002; PR = 2.271; 95%CI=1.491-3.459), and cardiomegaly (p = 0.011; PR = 1.722; 95%CI=1.151-2.577) with the reduced EF. In logistic regression analysis, arrhythmia (p = 0.009; PR = 4.191; 95%CI=1.426-12.320) was significantly associated with reduced EF. Kruskal-Wallis analysis showed a significant difference in white blood cell (p = 0.021), neutrophil (p = 0.027), and serum glutamic pyruvic transaminase (p = 0.013) in patients based on the EF. Conclusion: The comorbidity of CAD had a significant association with the reduced EF. Early intervention against this factor can improve the quality of management in the patient.